Prediksi Disleksia pada Anak menggunakan Metode Naive Bayes - Siti Alyunita Mega Lestari; Akim M.H. Pardede; Magdalena Simanjuntak (Institut Nalanda, 2024)
Dyslexia is a neurological disorder that affects a person's ability to read, spell, and understand words with a level of difficulty that is not in accordance with their level of intelligence or education. It is a lifelong condition that can affect the way the brain processes information related to reading and written language skills. This study uses the Naïve Bayes method. is a method that uses probability and statistical calculations. And the advantage of the Naïve Bayes classification is that this method only requires a small amount of training data to determine the parameter estimates needed in the classification process. The purpose of this study is to find out how to solve the diagnosis or problems arising from dyslexia in children made in an expert system using the Naïve Bayes method and to find out the results of making the system can replace an expert into a computer so that the diagnosis is easier and faster. The results of this study are by selecting the symptoms that occur in children according to what is experienced, the system can find out the child or patient can be diagnosed quickly according to consultation with a dyslexia expert.